2018
DOI: 10.1002/eat.22945
|View full text |Cite
|
Sign up to set email alerts
|

Improving motivation to change amongst individuals with eating disorders: A systematic review

Abstract: Motivation was found to increase across treatments in general, whether or not the focus of the intervention was on enhancing motivation. It is unclear if interventions specifically targeting motivation to change provide additional benefit over and above established treatment approaches.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
24
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 78 publications
(182 reference statements)
3
24
1
Order By: Relevance
“…This contemplation group intervention did not aim to improve participants' motivation for treatment directly, however, as the results of this evaluation show, the group seems to have led to an increase in motivation for some patients. This is in line with a recent study which showed that interventions that do not solely focus on motivation might be as effective at improving levels of motivation as interventions aimed specifically at motivation [24]. There have recently been some research proposals to review whether motivation to change is a useful indicator of treatment outcomes [25], as the literature currently offers mixed views on this [11,25].…”
Section: Discussionsupporting
confidence: 80%
“…This contemplation group intervention did not aim to improve participants' motivation for treatment directly, however, as the results of this evaluation show, the group seems to have led to an increase in motivation for some patients. This is in line with a recent study which showed that interventions that do not solely focus on motivation might be as effective at improving levels of motivation as interventions aimed specifically at motivation [24]. There have recently been some research proposals to review whether motivation to change is a useful indicator of treatment outcomes [25], as the literature currently offers mixed views on this [11,25].…”
Section: Discussionsupporting
confidence: 80%
“…Digital interventions have been identified as a potential approach to improving motivation to change among people with eating disorders [27]; our findings do not rule out this approach to addressing issues regarding low levels of treatment attendance. Indeed, both participants in the case studies suggested that, while MotivATE may not in and of itself be the solution, at least in its current form, the underlying concept remained a positive one.…”
Section: Discussioncontrasting
confidence: 73%
“…However, the attrition observed in the group condition (37.5%) appears higher than previous ED prevention groups (1–17%; McMillan, Stice, & Rohde, 2011; Stice, Butryn, Rohde, Shaw, & Marti, 2013). This could be because, compared with prior research, this study involved a lengthier time commitment (eight sessions vs. three to four) and lower participant incentive amounts ($5–15 compared with, for example, $30–150 per assessment; Denison‐Day, Appleton, Newell, & Muir, 2018; Stice, Rohde, Butryn, Shaw, & Marti, 2015, Stice, Shaw, Burton, & Wade, 2006).…”
Section: Discussionmentioning
confidence: 98%